2022
DOI: 10.3389/fphar.2022.1070802
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum cytokines and clinicopathological features in patients with drug-induced liver injury

Abstract: Objectives: Changes in serum levels of cytokines have been proposed as possible biological markers of tissue damage, including drug-induced liver injury (DILI). Here, we aimed to screen cytokine markers that have guiding significance for the degree of inflammation of DILI.Patients and methods: 54 patients with DILI were retrospectively analyzed as the experimental group, and 14 healthy subjects were randomly selected as the control group. A total of 20 cytokines were detected by using a cytokine protein antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…[ 4 , 5 ] In China, a retrospective study of 22,030 DILI patients showed that only 50.65% of them were cured, but 1.60% died. [ 6 ] Additionally, DILI is a potentially severe adverse drug reactions that is a major concern for healthcare systems and the pharmaceutical industry, with a cost of £1 billion in the United Kingdom and $4 billion in the United States. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 5 ] In China, a retrospective study of 22,030 DILI patients showed that only 50.65% of them were cured, but 1.60% died. [ 6 ] Additionally, DILI is a potentially severe adverse drug reactions that is a major concern for healthcare systems and the pharmaceutical industry, with a cost of £1 billion in the United Kingdom and $4 billion in the United States. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%